The role of midstream actors in vegetable value chains in Tanzania - Mvungi, Henry; Mlowe, Nickson; Ernest, Zablon; Mwambi, Mercy; Dijkxhoorn, Youri (World Vegetable Center, 2024)
This report presents the importance of recognizing and engaging midstream actors in transforming Tanzania's food system. Midstream actors provide essential market access to smallholder farmers, help matching supply with demand, and offer valuable market information to aid farmers' decision-making. However, issues such as preventing direct transactions between farmers and buyers, lack of market transparency, and unfair practices like the ‘rumbesa’ system, which demands extra payments from farmers, pose challenges. Informal retailers also play a crucial role, acting as intermediaries between farmers and consumers, ensuring efficient distribution and affordability. Food safety concerns, primarily related to chemical spraying, foodborne pathogens, and poor transportation conditions, were highlighted. Addressing these issues through improved packaging, better transport conditions, and fair-trading practices can reduce post-harvest losses and enhance quality. Recommendations for interventions include capacity building of farmers, promoting digitalization, enhancing midstream value chain actor capacity, introducing improved packing materials, regulating the market, conducting research, and also acknowledging the importance of the midstream segment. Implementing these strategies will contribute to a more resilient, efficient, and sustainable supply chain in Tanzania, benefiting all stakeholders. In the end, we aim to involve midstream actors as important change agents who can leverage the uptake of innovations.